Suszarnie solarne osadów ściekowych w Polsce = Solar dryers of sewage sludge in Poland - Trojanowska, Katarzyna; Sadecka, Zofia; Myszograj, Sylwia; Sieciechowicz, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper presents the evaluation of whether the construction of additional solar-heated drying of municipal sewage sludge on the basis of operational experience gained from working objects in Poland. It was indicated importance technical and technological aspects of drying sludge. In the national context, as shown in the example of sludge dryers in Zary, much more efficient and most importantly, cheaper is to use only solar sludge drying. Adequate space and technology equipment of halls drying can compensate for seasonal changes in the weather by changing the thickness of the sediment layer of solar drying.
Keywords: osady ściekowe; suszenie solarne; eksploatacja; koszty; sewage sludge; solar drying; operation; costs